Effects of Purple Rice Bran Addition on the Physicochemical-Sensorial Properties and Storage Stability of Chinese Sausage - Tatongjai, Kessinee; Laokuldilok, Thunnop (Journal of Food Technology, Siam University, 2018)
The aim of this research was to study the effect of addition of purple rice bran (0.25, 0.5 and 1%) on the properties and storage stability of Chinese sausage (at 4°C for 30 days). The results showed that Chinese sausage added with 1% purple rice bran had the highest antioxidant contents including 743 µgGAE/g of total phenolic, 14.99 µg/g of total anthocyanin, 18.09 µg/g of total tocopherols and 51.63 µg/g of gamma-oryzanol. Addition of purple rice bran did not affected the hardness, gumminess, and chewiness of the Chinese sausage; however, springiness and cohesiveness of Chinese sausage with 1% addition were slightly decreased. Sensory evaluation showed that color, odor, flavor and overall liking scores of Chinese sausage added with purple rice bran were not significantly different from the control. After 30 days of storage time at 4°C, the thiobarbituric acid (TBA) value of Chinese sausage added with 1% purple rice bran (0.39 µg/g) was lower than that of the control (2.13 µg/g). It indicated that the antioxidants in purple rice bran retarded the lipid oxidation during a period of storage.